2017
DOI: 10.1038/s41598-017-05290-4
|View full text |Cite
|
Sign up to set email alerts
|

A tyrosine aminotransferase involved in rosmarinic acid biosynthesis in Prunella vulgaris L

Abstract: Rosmarinic acid (RA) and its derivants are medicinal compounds that comprise the active components of several therapeutics. We isolated and characterised a tyrosine aminotransferase of Prunella vulgaris (PvTAT). Deduced PvTAT was markedly homologous to other known/putative plant TATs. Cytoplasmic localisation of PvTAT was observed in tobacco protoplasts. Recombinantly expressed and purified PvTAT had substrates preference for L-tyrosine and phenylpyruvate, with apparent K m of 0.40 and 0.48 mM, and favoured th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 71 publications
2
25
0
1
Order By: Relevance
“…However, various reports indicate the role of one of two branching pathways in the biosynthesis of rosmarinic acid. Some of them showed that the biosynthesis of RA and phenolic compounds were correlated with TAT but not PAL activity (for example: Yan et al 2006; Lu et al 2013; Zhang et al 2014; Ru et al 2017), and the others conversely showed the involvement of PAL-derived pathway (for example: Mizukami et al 1992; Kim et al 2013). TAT is presumed to have a role in RA accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, various reports indicate the role of one of two branching pathways in the biosynthesis of rosmarinic acid. Some of them showed that the biosynthesis of RA and phenolic compounds were correlated with TAT but not PAL activity (for example: Yan et al 2006; Lu et al 2013; Zhang et al 2014; Ru et al 2017), and the others conversely showed the involvement of PAL-derived pathway (for example: Mizukami et al 1992; Kim et al 2013). TAT is presumed to have a role in RA accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, an opium poppy (Papaver somniferum) TAT was shown to participate in the production of benzylisoquinoline alkaloids, including morphine and codeine (Lee and Facchini 2011). In Prunella vulgaris, a Traditional Chinese Medicinal (TCM) plant in the family of Lamiaceae, TAT is involved in the biosynthesis of RA (Ru et al 2017).…”
Section: The General Tyrosine Metabolism Pathwaymentioning
confidence: 99%
“…In this study, we identified six phenolic acids from WHT, and they all exhibited high antioxidant activity, which is consistent with the results from previous research [ 14 , 23 , 24 ]. Among these phenolic acids, rosmarinic acid had the highest content and the highest contribution ratio to the antioxidant activity of WHT, which is a major component of Prunella vulgaris (a raw material of WHT) [ 25 ]. However, total antioxidant activity of all six phenolic acids only contributed to 9.6% of DPPH radical scavenging activity and 13.6% of FRAP activity of WHT.…”
Section: Discussionmentioning
confidence: 99%